Main metals composition (wt % of dried substance) for manganese crusts retrieved in the Pacific Ocean during the SO-18 (MIDPAC 1) campaign - Peter Halbach; M Segl; Doris Puteanus; Augusto Mangini (PANGAEA, 2023)
Manganese crust samples were dredged from the Line Islands Ridge and the MidPacific Mountains that were recently taken during the R/V Sonne SO18 (Midpac 81) cruise. The metal composition of the outermost millimetre of the crusts where growth rates were determined is given in Table 1. The concentrations were measured on dried substance. Mn, Fe were determined by potentiometric and complexometric titration methods; Ni, Cu, Co were analysed using differential pulse polarography. All analytical data are results of repeated determinations having <1% of relative error for main constituents (Mn, Fe), and <5% of relative error for minor constituents (Ni, Co, Cu).